ABORSI DALAM PERSPEKTIF HUKUM ISLAM (SUATU ANALISIS DENGAN PENDEKATAN FIQH AL-MUQÃRIN) - Jumat, Abd. Gani (Institut Agama Islam Negeri (IAIN) Palu, 2008)
Abortion is one of the contemporary law problems frequently debated. In Indonesia, abortion is not only a law problem but also a moral problem. Posing abortion within the law and moral perspective bocomes important since it is related to the lawÂ dealing with the termination of a childâs right to life. This article deals with the status ofÂ abortion within the Islamic law and moral perspective, employing the method of fiqh al-muqÃ¢rin (comparative fiqh), that is by comparing and conforming the ikhtilÃ¢f of abortion amongst the jurists (fuqahÃ¢â). After analyzing the juristsâ opinions of abortion, the writer found that since sperms and ovums come together and pertlization occurs, abortion is judged as a crime, and therefore the law status of which is proscribed.Kata Kunci: Â aborsi, hukum Islam, moral